Development of power supply using solar energy for smart agriculture system - Alhafizul, Ibnohasim (2022)
The agriculture sector must undergo daily monitor that need to tun in precise time to ensure the good quality of the production. To running IoT system for smart agriculture system must unsing the power supply to component can using. This study aim to develop power supply for smart agriculture system and use it in real environment using solar energy. To make this system function, you'll need a solar panel, solar charger controller, battery, DC to DC converter, load, and wire. The reading load can be uploaded into the system and displayed through the application or website once all of the components have been brought together. Current will flow from the power source to the WiFi UNO and straight to the sensor, allowing the sensor's measurements to be displayed and the solenoid valve to open for 7 minutes for each unit. If the sensor reading differs from the necessary value, we may use the system to direct the solenoid valve to open. When data can be transferred and monitor on the application and web site, and the solenoid valve can function properly, solar can be guaranteed to work to supply current to all component.